SELF-PERCEIVED HEALTH OF THE ELDERLY: ECONOMIC AND SOCIODEMOGRAPHIC INEQUALITIES - Olga GAGAUZ; Cristina AVRAM; Irina PAHOMII (Economy and Sociology, 2017)
Given the rapid increase in the number and share of the elderly in the total population, good healthand healthy ageing are an important factor in the socio-economic development of ageing societies. Selfperceivedhealth is one of the most important health and well-being indicators. The article presents theresults of research on self-perceived elderly health based on data from "Household Budget Survey" for2006-2015 (NBS). The study reveals a slow increase in life expectancy and healthy life expectancy, as wellas time spent in good health. The life expectancy without chronic illness is lower than healthy lifeexpectancy. There is a positive rise in the self-assessment of the elderly for both sexes and at different agesafter 60 years. The regression analysis of factors influencing self-perceived health (age, sex, education level,welfare level, degree of disability and civil status), demonstrates that among the most important factors withwhich self-responding health is associated, as bad and very bad were highlighted the low level of educationand material welfare, as well as the presence of behavioural vices (smoking).